A comprehensive review of arginine kinase proteins: What we need to know? - Brenda Martins Vasconcellos; Victor Guimarães Ribeiro; Naysha do Nascimento Campos; Luis Guilherme da Silva Romão Mota; Mônica Ferreira Moreira (Biochemistry and Biophysics Reports)
The enzyme arginine kinase (AK), EC 2.7.3.3, catalyzes the reversible phosphorylation of arginine with adenosine triphosphate, forming phosphoarginine, which acts as an energy reservoir due to its high-energy phosphate content that can be rapidly transferred to ADP for ATP renewal. It has been proposed that AK should be associated with some ATP biosynthesis mechanisms, such as glycolysis and oxidative phosphorylation. Arginine kinase is an analogue of creatine kinase found in vertebrates. A literature survey has recovered the physicochemical and structural characteristics of AK. This enzyme is widely distributed in invertebrates such as protozoa, bacteria, porifera, cnidaria, mollusca, and arthropods. Arginine kinase may be involved in the response to abiotic and biotic stresses, being up regulated in several organisms and controlling energy homeostasis during environmental changes. Additionally, phosphoarginine plays a role in providing energy for the transport of protozoa, the beating of cilia, and flagellar movement, processes that demand continuous energy. Arginine kinase is also associated with allergies to shellfish and arthropods, such as shrimp, oysters, and cockroaches. Phenolic compounds such as resveratrol, which decrease AK activity by 50 % in Trypanosoma cruzi, inhibit the growth of the epimastigote and trypomastigote forms, making them a significant target for the development of medications for Chagas Disease treatment.